Review of Sangri (Prosopis Cineraria Pods) - A Rich Protein Source of Rajasthani Cuisine. - Yadav, Natasha; Choudhury, Monjoy Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Even though Indian cuisines are famous worldwide for its culinary flavours but it is to be noted that the ingredients of Indian cuisines also possess medicinal properties as well as nutritive value. Unlike the western cuisines where meat dominate dietary protein, in India certain edible common plants provide both protein and medicinal properties. Prosopis cineraria is one such plant belonging to Fabaceae family whose fruits are unique to the dry arid regions of the Indian state of Rajasthan. The fruit of the plant which is commonly called as Sangri is a common vegetable regularly consumed by the locals of Rajasthan. Since the plant had been extensively mentioned in ayurveda in this review we would explore the presence of various molecules with medicinal properties and how it prevents diseases while remaining hidden as part of our food habit.